Kenya Climate Smart Agriculture (CSA) Multi-Stakeholder Platform reaches farmers with CSA options through 35 member organizations - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
The Kenya Climate Smart Agriculture Multi-Stakeholder Platform (CSA MSP) has continued to flourish after its establishment in 2019. The number of member organizations has grown, a website has been set up, and a five-year strategic plan (2022-2026) will be launched in January 2022. Member organizations have stepped forward to provide funding for the establishment of county-level MSPs for reaching more farmers on the ground. There are now 35 official member organizations.